THE EFFECTIVENESS OF POSITIVE SELF-TALK THERAPY IN REDUCING ANXIETY AMONG ADOLESCENTS WHO EXPERIENCE EMOTIONAL ABUSE: A LITERATURE REVIEW - Meiti Subardhini; Septyan Berliana Sumaki; Sabar Riyadi (ADISAM Publisher, 2026)
Anxiety is one of the psychological problems commonly experienced by adolescents, particularly among those who have been exposed to emotional abuse. Emotional abuse, including insults, threats, yelling, rejection, humiliation, intimidation, and persistent invalidation, can shape negative internal schemas, reduce self-esteem, and intensify fear, insecurity, and avoidance. Recent international studies published after 2023 indicate that childhood maltreatment and emotional abuse are consistently associated with adolescent anxiety, psychopathology, impaired emotion regulation, and heightened psychological distress (Hashim et al., 2024; Baldwin et al., 2024; Chen et al., 2025). This literature review examines the potential effectiveness of positive self-talk therapy in reducing anxiety among adolescents who experience emotional abuse. The review was conducted by identifying and synthesizing scientific articles, international journals, national journals, and official reports relevant to positive self-talk, adolescent anxiety, emotional abuse, coping, cognitive restructuring, and emotion regulation. The findings suggest that positive self-talk therapy may help adolescents recognize negative internal dialogue and replace it with more rational, supportive, adaptive, and goal-oriented statements. The mechanism of change is closely related to cognitive reframing, self-compassion, affect labeling, and emotion regulation, all of which are important protective processes in adolescent mental health. Therefore, positive self-talk therapy may serve as a simple, low-cost, school- and community-based psychosocial intervention to support adolescent mental health. However, further empirical studies using stronger designs, such as randomized controlled trials or quasi-experimental designs with control groups, are needed to test its effectiveness specifically among adolescent victims of emotional abuse.